Enhanced Recovery After Surgery for patients undergoing radical cystectomy: Surgeons' perspectives and recommendations ten years after its implementation - Albisinni, Simone; Orecchia, Luca; Mjaess, Georges; Aoun, Fouad; Del Giudice, Francesco; Antonelli, Luca; Moschini, Marco; Soria, Francesco; Mertens, Laura S; Gallioli, Andrea; Marcq, Gauthier; Pradere, Benjamin; et al. (European journal of surgical oncology, 2025)
BACKGROUND AND OBJECTIVES: Enhanced Recovery After Surgery (ERAS) guidelines for Radical Cystectomy (RC) were published over ten years ago. Aim of this systematic review is to update ERAS recommendations for patients undergoing RC and to give an expert opinion on the relevance of each single ERAS item. METHODS: A systematic review was performed to identify the impact of each single ERAS item on RC outcomes. Embase and Medline (through Pubmed) were searched systematically. Relevant articles were selected and graded. For each ERAS item, a level of evidence was determined. An e-Delphi consensus was then performed amongst an international panel with renowned experience in RC to provide recommendations based on expert opinion. KEY FINDINGS AND LIMITATIONS: Preoperative medical optimization and avoiding bowel preparation are highly recommended. Robotic-assisted RC with intracorporeal urinary diversion is moderately recommended and can help in applying other ERAS items, such as early mobilization. Medical thromboprophylaxis should be administered and nasogastric tube should be removed at the end of surgery. Perioperative fluid restriction as well as opioid-sparing anesthesia protocols should be implemented. Generally, consensus was reached on most ERAS items, with the exception of epidural anesthesia (no consensus), resection site drainage (consensus against), and type of urinary drainage. Limitations include the lack of a multidisciplinary approach to the present consensus, giving however a highly specialized surgical opinion on ERAS. CONCLUSIONS: and clinical implications: The current study updates ERAS recommendations for patients undergoing RC and suggests application of ERAS by a panel of experts in the field.
Keywords: časné pohybování; nádory močového měchýře; diverze moči; chirurgové; roboticky asistované výkony; urychlená pooperační rehabilitace; Robotic Surgical Procedures; Cystectomy; Early Ambulation; cystektomie; Urinary Bladder Neoplasms; lidé; Practice Guidelines as Topic; Surgeons; Urinary Diversion; Humans; Enhanced Recovery After Surgery; směrnice pro lékařskou praxi jako téma